2022
DOI: 10.3390/cells11203230
|View full text |Cite
|
Sign up to set email alerts
|

Adipokines as Regulators of Autophagy in Obesity-Linked Cancer

Abstract: Excess body weight and obesity have become significant risk factors for cancer development. During obesity, adipose tissue alters its biological function, deregulating the secretion of bioactive factors such as hormones, cytokines, and adipokines that promote an inflammatory microenvironment conducive to carcinogenesis and tumor progression. Adipokines regulate tumor processes such as apoptosis, proliferation, migration, angiogenesis, and invasion. Additionally, it has been found that they can modulate autopha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 163 publications
0
3
0
Order By: Relevance
“…It has been reported that leptin can modify the process of autophagy and favor leptin-driven tumor development and growth 26 . To demonstrate the involvement of autophagy in some of the leptin-induced cancer characteristics, we first determined the effect of leptin on autophagy in breast cancer cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that leptin can modify the process of autophagy and favor leptin-driven tumor development and growth 26 . To demonstrate the involvement of autophagy in some of the leptin-induced cancer characteristics, we first determined the effect of leptin on autophagy in breast cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…Since leptin was shown to induce autophagy in healthy peripheral tissues, the interest has grown in elucidating the role of autophagy in leptin-driven malignant features of obesity-linked cancer 26 . Postmenopausal breast cancer is one of the malignancies associated with obesity in women.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, chronic inflammation in adipose tissue is stimulated and maintained by nuclear factor kB (NFkB) causing a pro-oncogenic environment [200]. Of the adipokines that have been characterized, leptin, resistin, visfatin, and apelin are abundant in the plasma of obese individuals, while adiponectin concentrations are minimal in obese individuals [201]. However, a recent meta-analysis established that adiponectin and leptin were the most studied, while interleukin-6, tumor necrosis factor-alpha, and resistin were relatively less studied [197].…”
Section: Adipokines and Cancermentioning
confidence: 99%
“…According to leptin, it has been postulated as a potential overexpressed biomarker in breast tumors and metastatic lesions in women [202]. Leptin is a 16 kDa polypeptide produced mainly from white adipose tissue, and its plasma concentration directly correlates with the amount of that tissue [201]. Leptin binds to its receptors encoded by the LEPR gene, which is composed of six isoforms belonging to the cytokine receptor family [12].…”
Section: Adipokines and Cancermentioning
confidence: 99%
“…The over-activation of ObRb leads to an increase in signaling in the JAK2/STAT3, PI3K, and ERKs pathways, which modulate the expression of genes related to cancer such as vascular endothelial growth factor (VEGF), cyclin D1, and cyclooxygenase-2 that favor angiogenesis, cell proliferation, and migration processes [ 216 ]. Leptin can also promote changes in the inflammatory environment by increasing the expression and secretion of different cytokines, which leads to increased migration and invasion of cancer cells in different organs [ 217 ]. Leptin may have synergistic actions with other cytokines in different types of cancers.…”
Section: Functionality Of Leptin and Its Involvement In Pathologymentioning
confidence: 99%